Survey for zoonotic pathogens in Norway rat populations from Europe. Issue 2 (29th July 2016) - Heuser, Elisa; Fischer, Stefan; Ryll, René; Mayer‐Scholl, Anne; Hoffmann, Donata; Spahr, Carina; Imholt, Christian; Alfa, Dewi Murni; Fröhlich, Andreas; Lüschow, Dörte; Johne, Reimar; Ehlers, Bernhard; et al.
Abstract: BACKGROUND: The Norway rat Rattus norvegicus is an important reservoir of various zoonotic pathogens, such as cowpox virus and Leptospira, but also for agents of no or unknown zoonotic potential. We describe a survey of 426 Norway rats originating from five European countries and different habitats for Leptospira spp., rickettsiae, orthopoxvirus (OPV), avian metapneumovirus subtypes A and B (aMPV) and rat polyomavirus (rat PyV). RESULTS: Leptospira DNA was detected in 60 out of 420 (14.3%) rats, and Rickettsia DNA was found in three out of 369 (0.8%) rats investigated. PCR‐based typing resulted in the identification of L. interrogans sequence type 17, which corresponds to the serogroup Icterohaemorrhagiae, and Rickettsia helvetica respectively. Rat PyV DNA was detected in 103 out of 421 (24.5%) rats. OPV DNA and aMPV RNA were detected in none of the rats, but OPV‐specific antibodies were detected in three out of 388 (0.8%) rats. The frequency of single Leptospira and rat PyV infections and coinfections was, independent of sex, greater for adults compared with juveniles/subadults and greater at rural sites compared with urban areas. CONCLUSIONS: Study results indicate a broad geographical distribution of Leptospira DNA in rats within Europe, underlining the need to investigate further the potential mechanisms leading to increased prevalence in rural habitats and to assess the relevance to public health. In contrast, rickettsia and OPV infections rarely occurred in wild rat populations. The potential influence of rat PyV on the susceptibility to infections with other pathogens should be investigated in future studies. © 2016 Society of Chemical Industry